Pengaruh Coaching dan Mentoring terhadap Perkembangan Umkm Fashion Serta Orientasi yang Dimediasi Kewirausahaan - Sendy Zul Friandi; Suwarto Suwarto; Danang Rifai (COSTING : Journal of Economic, Business and Accounting, 2020)
Changes in the environment and market mechanisms that are so open, competitive, and market control are challenges that must be answered with a market orientation approach. The purpose of this study is: to examine the effect of coaching and mentoring on the development of Fashion Micro, Small and Medium Enterprises (MSMEs) in the capital's supporting areas. This research was conducted at MSME Fashion conducted by young men and women of the millennial generation. While the study population was reviewed at MSME Fashion in the Greater Tangerang area. The sample of this study consisted of 74 MSME Fashion Distros in Tangerang Regency, Tangerang City and South Tangerang City. The sampling technique is multistage sampling consisting of the first simple random sampling in order to determine the Greater Tangerang area that has MSME Fashion, the second is purposive sampling in order to determine the sample in each mapping area that has been determined as a member of the coaching and mentoring of the local entrepreneurship body, and the third is convenience sampling. The method used in determining the sample is based on respondents selected in stage two who are willing to attend. The statistical methods used by researchers are the Confirmatory Factor Analysis (CFA) Method for testing validity, the Cronbach Alpha Method for reliability testing, and the Baron and Kenny methods for hypothesis testing, statistical calculations are performed using the MINITAB application. In this study, researchers found a research result that showed that coaching and mentoring had a positive effect on the development of Fashion MSMEs and the Regional Entrepreneurship Agency played a positive role in mediating the development of MSMEs. Keywords: Coaching, Mentoring, Development of SMEs